(3GdHjGf aj abg GdTGaYjIs - (3jMji Hf SGde Hf CSYO Hf jMji, CHh GdMSjf GdYeQGfj,J (B558 (3g` s
(3ChdgG (B:s
(3cJGH GdLfGjGJ , HGH JMQje GdbJd hef jLH Ydjg GdbUGU (B: (3hef dG jLH Ydjg GdbJd HZjQ Mb MQGe , hGdCUd ajg GdcJGH hGdSfI s
(3BNQgG (B:s
(3hcGfJ GdLGQjI Ydi eG KHJ dgG ef MQeI GdESJjdGO , hGdhdO Ydi eG KHJ dg ef GdMQjI , hHGddg GdJhajb hgh MSHfG hfYe Gdhcjd s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3abg CFeI GdePGgH (B481) s
Keywords: (3Gdabg GdTGaYjs